A Brief Review on Working Fluid Wastewater Treatment: A Glance at the Disposal of Exhausted Fluids Used in the Organic Rankine Cycle - Mohammad Mehdi Golbini Mofrad; Mika Sillanpää; Iman Parseh; Afshin Ebrahimi; Mohammad Mehdi Amin (Shiraz University of Medical Sciences, 2022)
Background: Treating working fluid wastewater (WFW) by having several organic/inorganic pollutants is not an easy task. There are many hurdles to adopt an appropriate treatment strategy through biological, physical, chemical, and electrochemical approaches. Methods: The treatment methods of WFW are reviewed in this work through a critical literature survey. Therefore, databases such as Google scholar, science direct, and PubMed were considered to find literature. Altogether, about 49 articles were finally found relevant to the topic to extract and interpret findings. Results: The best solution to treat WFW could be an integrated approach by designing various AOPs for the pre-treatment and post-treatment of main units. For this reason, and to meet discharge standards, measuring intermediates and the toxicity of reaction solution and final effluent by bioassay could be a complementary tool. Additionally, if the used AOP is a photocatalytic one, applying catalysts with a low energy bandgap and designing reactors to utilize the highest amount of energy is crucial to make a process cost-effective. Furthermore, using aeration could increase the number of radicals by supplying oxygen and removing contaminants from the reaction medium. Finally, if AOPs are the pretreatment unit, removing halogens should be done to predict floc breakage in the next step. Conclusion: Hybrid treatment approaches with at least 80% efficiency in degrading and removing micropollutants could be reliable methods to dispose of working fluid wastewater. However, further research on them in the future is essential because of discharging a considerable volume of them annually worldwide.